Making a ternary logic table, and I would like to make my own function for an operator that I'll call <=>
.
So, for example, I want to do this, but that isn't right. what's the correct way to do this?
data Ternary = T | F | M
deriving (Eq, Show, Ord)
<=> :: Ternary -> Ternary -> Ternary
<=> T F = F
<=> T T = T
<=> T M = M
<=> F F = T
<=> F T = F
<=> F M = M
<=> M F = M
<=> M T = M
<=> M M = T
Just add parentheses around your operator:
(<=>) :: Ternary -> Ternary -> Ternary
(<=>) T F = F
(<=>) T T = T
(<=>) T M = M
(<=>) F F = T
(<=>) F T = F
(<=>) F M = M
(<=>) M F = M
(<=>) M T = M
(<=>) M M = T
This turns it from infix form to prefix form. Alternatively, you can just use infix in the definition:
(<=>) :: Ternary -> Ternary -> Ternary
T <=> F = F
T <=> T = T
T <=> M = M
F <=> F = T
F <=> T = F
F <=> M = M
M <=> F = M
M <=> T = M
M <=> M = T
Function names with symbols have different syntax than those without:
-- Works:
(<^>) :: Int -> Int -> Int
a <^> b = a + b
-- Doesn't work:
{-
<^> :: Int -> Int -> Int
<^> a b = a + b
-}
-- Works:
letters :: Int -> Int -> Int
letters a b = a + b
-- Doesn't work:
{-
(letters) :: Int -> Int -> Int
a letters b = a + b
-}
I promise, though - Haskell is well worth learning the complex rules.
You can simplify (line-wise) the definition as follows:
(<=>) :: Ternary -> Ternary -> Ternary
T <=> T = T
F <=> F = T
M <=> M = T
M <=> _ = M
_ <=> M = M
_ <=> _ = F
Since you have Eq
and Ord
, you can do the following:
data Ternary = T | F | M
deriving (Eq, Show, Ord)
(<=>) :: Ternary -> Ternary -> Ternary
x <=> y = if x == y then T else max x y
If you do happen to change it so that M <=> M == M
, then you can do the following:
data Ternary = M | T | F
deriving (Eq, Show, Ord, Enum)
(<=>) :: Ternary -> Ternary -> Ternary
x <=> y = fromEnum $ rem (toEnum x * toEnum y) 3
来源:https://stackoverflow.com/questions/9356442/how-do-i-create-an-operator-in-haskell